1996
DOI: 10.1111/j.1574-6968.1996.tb08411.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization ofBorreliasp. isolated fromIxodes tanuki,I. turdus, andI. columnaein Japan by restriction fragment length polymorphism ofrrf(5S)-rrl(23S) intergenic spacer amplicons

Abstract: Borrelia isolated from various sources in Japan, including rare species of ixodid ticks, Ixodes tanuki, I. turdus, and I. columnae, were characterized by restriction fragment length polymorphism analysis and sequencing analysis of the 5S-23S rRNA intergenic spacer amplicon. Borrelia sp. isolated from I. tanuki, I. turdus and I. columnae generated restriction fragment length polymorphism patterns different from those of known B. burgdorferi sensu lato isolates previously reported. Furthermore, some B. afzelii a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

1999
1999
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(13 citation statements)
references
References 23 publications
0
11
0
2
Order By: Relevance
“…garinii (26.2%) with prevalence rates in correspondence with data from neighboring regions Russia [40], Finland [41] and Latvia [38]. Several studies from Europe indicate a wide spread of B. afzelii and its subgroups NT28 and VS461 [19,25] in different regions of Europe and Asia as well as in different vector species [27,42]. The fact that both genetic groups of B .…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…garinii (26.2%) with prevalence rates in correspondence with data from neighboring regions Russia [40], Finland [41] and Latvia [38]. Several studies from Europe indicate a wide spread of B. afzelii and its subgroups NT28 and VS461 [19,25] in different regions of Europe and Asia as well as in different vector species [27,42]. The fact that both genetic groups of B .…”
Section: Discussionmentioning
confidence: 66%
“…Analysis of nucleotide sequences showed that the investigated samples belong to two genomic subgroups of B . afzelii , VS461 and NT28 [25-27], that were detected in 62.6% and 28.6% of all B . afzelii positive ticks, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The B. garinii NT29 group is widely spread not only in Western Siberia but in the Russian Far East (GenBank accession no. AY429014, AY429015), Japan ( 34 , 35 ), and China ( 36 ). The nested PCR with subsequent sequencing allowed us to detect DNA of B. garinii group NT29 in 3.6% ± 2.0% of D. reticulatus ticks.…”
Section: Discussionmentioning
confidence: 99%
“…Representative DNA samples prepared from tick tissue were subjected to additional method for detection of B. burgdorferi s.l.rrf-rrl rDNA intergenic spacer PCR. Primers corresponding to the 3' end of 5S rDNA (rrf) (RIS1; 5'-CTG CGA GTT CGC GGG AGA-3' and RIS3; 5'-GGA GAG TAG GTT ATT GCC AGG-3') and the 5' end of 23S rDNA (rrl) (RIS2; 5'-TCC TAG GCA TTC ACC ATA-3' and RIS4; 5'-GAC TCT TAT TAC TTT GAC C-3') were used for fi rst-step (RIS1 and RIS2) and nested-PCR (RIS3 and RIS4) under the previously described PCR conditions (Masuzawa et al, 1996). Th e quality of extracted DNA was evaluated by PCR targeted to the internal transcribed spacer 2 (ITS2) region of tick-ribosomal DNA genes according to a previously described method (Radulović et al, 2010).…”
Section: Detection Of B Burgdorferi Sl Dnas In Tick Samples By Conventional Pcrmentioning
confidence: 99%